The Role of Alpha-Tocotrienol during Development of Primary Hippocampal Neurons. (14th June 2022) - Park, Han-A; Crowe-White, Kristi; Ciesla, Lukasz; Bannerman, Sydni; Scott, Madison; Davis, Abigail; Adhikari, Bishnu; Burnett, Garrett; Broman, Katheryn; Ferdous, Khondoker Adeba; Lackey, Kimberly; Lickznerski, Pawel; et al.
Abstract: Objectives: Alpha-tocotrienol (α-TCT), a form of vitamin E, is a lipophilic antioxidant with neuroprotective properties. We recently reported that α-TCT treatment prevents oxidative stress-induced proteolytic cleavage of B-cell lymphoma-extra large (Bcl-xL), a pro-survival mitochondrial protein necessary during neuronal growth. However, it is still unclear if α-TCT exhibits beneficial effects during the physiological development of neurons. In this study, we hypothesized that chronic α-TCT treatment advances the development of primary hippocampal neurons by improving mitochondrial function. Methods: Primary rat hippocampal neurons were grown in neurobasal media with or without α-TCT for three weeks, and media was replaced with conditioned media containing fresh α-TCT every week. Intracellular α-TCT levels were quantified using HPLC-MS, and intracellular ATP and mitochondrial superoxide levels were determined using luciferase and mitoSOX, respectively. Neurite morphology was examined by Sholl analysis. mRNA and protein levels of Bcl-xL were quantified using qPCR and immunoblotting, respectively. Results: Primary hippocampal neurons grown in media containing α-TCT had increased intracellular α-TCT levels and decreased mitochondrial superoxide. Treatment with α-TCT increased mRNA and protein levels of Bcl-xL, neuronal ATP, and the number of neurite branches in primary hippocampal neurons. Conclusions: We found that primary rat hippocampal neurons treated with α-TCT developed advanced neurite complexity. We suggest that α-TCT treatment improves mitochondrial function via upregulation of Bcl-xL, supporting normal neuron development. Funding Sources: RGC Program (University of Alabama); Crenshaw Research Fund (University of Alabama).